Health care monitoring using wireless sensor network (H-Caring) - Nik Nur Farah Ayu , Che Hamid (2012)
The development of Health Care Monitoring Using Wireless Sensor Network is an ultimate solution to achieve the goal of universal health care for everybody due to accidents and various diseases. This project can measure several medical parameters such as body temperature, oxygen percentage in blood and heartbeat. All the parameters will be displayed on Personal Computer (PC) at centre unit by using GUI!. This project consists of two parts which are hardware design and software development. The hardware design is divided to two modules; slave module for measurement of several parameters of patient and master module for collecting real time parameters. Zigbee technology is preferred in the wireless communication design due to effectiveness, performance, and durability. Two different types of microcontroller are used to control the operation of control center and remote. Global System for Mobile (GSM) features in the design to relay the message automatically to authorized user about the condition of patients.